Translation of the Taboo Word ‘fuck’ as A Linguistic Approach in ELT: The Case of Everything is F*cked and Segala-galanya Ambyar - Pendi Lestiani Novita Putri (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The word 'fuck' is one of the taboo words in English and the research of its translation into Indonesian has been little conducted. This research aims to investigate the translation of ‘fuck’ and its compounds (e.g.motherfuck) and derivatives (e.g.fucking) into Indonesian. The data are collected from a bestselling book Everything is F*cked by Mark Manson which has been translated as Segala-galanya Ambyar. The method used is a descriptive method by sorting out the variations of fuck and their translation and by analyzing them based on grammatical categories of usage and translation strategies. The result shows variations of fuck are used in 12 grammatical categories: (1) adverbial booster; (2) curse expletive; (3) destinational usage; (4) emphatic adverb/adjective; (5) figurative extension of literal meaning; (6) general expletive; (7) idiomatic “set phrase”; (8) literal usage; (9) predicative negative adjective; (10) ‘pronominal’ form with undefined referent; (11) personal insult referring to defined entity; and (12) premodifying intensifying negative adjective. The analysis on grammatical structures and the lexical meaning analysis disclose that variations of ‘fuck’ impart emotive expressions such as dissatisfaction, emphasis, contempt, and excitement. These emotions take part in determining their translation strategies. Further analysis shows that euphemism, discursive creation, transfer, and omission, are the significant strategies used in this case. Essentially, this method of research could be an effective method to teach the usage of English taboo words – especially ‘fuck’, on lexical and contextual dimensions.